INFORMATION AND COMMUNICATION TECHNOLOGIES: AN EMERGING CONCEPT IN NURSES ’PRACTICES IN BASIC CARE: INFORMATION AND COMMUNICATION TECHNOLOGIES: AN EMERGING CONCEPT IN NURSES ’PRACTICES IN BASIC CARE - da Silva Nascimento, Bruno Rafael; de Quental, Ocilma Barros; Bezerra, Yuri Charllub Pereira; Feitosa , Ankilma do Nascimento Andrade; Silva Oliveira , Geane; Medeiros, Renata Lívia Fonseca Moreira de (Brazilian Journal of Production Engineering, 2020)
The technological insertion in the health field is notorious, as these resources are innovative before preventive actions and care. Nursing in the globalized world has instruments that can optimize its service. Therefore, the objective of this research is to analyze how ICTs can favor nursing care in primary care, making the service more agile and organized. This is an integrative review study that used digital databases by crossing the descriptors: “information and communication technologies”, “primary care” and “nursing care”. The search returned 335 articles, of which 9 were excluded due to duplication and 215 because they did not meet the inclusion criteria, leaving 111 articles. After the analysis, 12 articles were included in this review. In the sample, publications in national journals with more than 4 authors prevailed. Note: 5 methodological studies applied to the development of technological assistance equipment, 5 exploratory studies of a descriptive character (qualitative/ quantitative) and 2 case studies. ICTs are present and necessary instruments in the health service. Digital resources should be explored by nurses because they enhance nursing care, being useful in management and assistance. However, they are little disseminated due to the lack of qualification in the area of ​​technology and information technology.